Estimating and monitoring seasonal water consumption of olive orchards in a semi-arid region (Morocco) using the Eddy-covariance system - Ezzahar J.; Chehbouni A.; Er-Raki S.; Khabba S.; Hanich L. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Accurate measurements of heat and water fluxes are required for optimizing water management and for validating models simulating crop water consumption. For the olive orchard, which is the dominant crop in Mediterranean regions, very little information exists on the exchange of heat and water fluxes between the vegetation and the atmosphere. In the context of SUDMED project, an experimental setup was conceived to monitor seasonal water consumption of olive orchards located near Marrakech, Morocco. For this purpose, an Eddy-Covariance (EC) system, a meteorological station, as well as measurements of soil moisture and temperature were continuously operated during more than one year over an irrigated olive yard, i.e. tall, sparse vegetation. The total annual rainfall and irrigation amount were around 354 and 800 mm respectively. The yearly cumulative evapotranspiration measured from eddy-covariance system was 824 mm. By using the water balance equation, the result showed also that a large quantity of water (around 330 mm) was lost due to deep percolation, infiltration and runoff. This loss is essentially due to the irrigation method (flood) which has an irregular pattern in space and time. On the other hand, the water requirements calculated following the FAO-56 procedure were 920 mm. Although the sum of irrigation and rainfall was greater than ETc, the stress event occurred. Such behaviour can be explained by the fact that the irrigation monitoring is done by observing the physical conditions of the plant which is not sufficient to manage the irrigation.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)